2008
DOI: 10.1093/treephys/28.10.1459
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of flowering genes and seasonal changes in their transcript levels related to flower induction and initiation in apple (Malus domestica)

Abstract: Flower development in apple (Malus domestica Borkh.) extends over two consecutive seasons. During the first season, most shoot apical meristems change to reproductive growth and initiate flowers. After winter dormancy, flower development continues during the second season and ends with anthesis in the spring. To determine the beginning of the transition to reproductive growth at the molecular level and to identify genes involved in this critical phase of flower development, we examined transcript levels of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 34 publications
2
38
0
Order By: Relevance
“…Because there is a lack of information on the relationship between AGL6 homologs and seasonal flower initiation, seasonal changes in MdMADS11 gene expression were analyzed in adult apple trees. A rapid decrease in the abundance of MdMADS11 mRNA in leaf buds with putative seasonal flower initiation is interesting because MdMADS11 may promote flowering; however, unlike that described for MdFT (Hättasch et al, 2008;Kotoda et al, 2010) no peak in flower buds was detected in MdMADS11 expression, suggesting that other factors are involved in the control of seasonal flower initiation. In addition, AGL6 homologs may play a role in floral organ formation, as described in orchids, petunia, and rice (Hsu et al, 2006;Ohmori et al, 2009;Rijpkema et al, 2009).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Because there is a lack of information on the relationship between AGL6 homologs and seasonal flower initiation, seasonal changes in MdMADS11 gene expression were analyzed in adult apple trees. A rapid decrease in the abundance of MdMADS11 mRNA in leaf buds with putative seasonal flower initiation is interesting because MdMADS11 may promote flowering; however, unlike that described for MdFT (Hättasch et al, 2008;Kotoda et al, 2010) no peak in flower buds was detected in MdMADS11 expression, suggesting that other factors are involved in the control of seasonal flower initiation. In addition, AGL6 homologs may play a role in floral organ formation, as described in orchids, petunia, and rice (Hsu et al, 2006;Ohmori et al, 2009;Rijpkema et al, 2009).…”
Section: Discussionmentioning
confidence: 83%
“…FT homologs may play a role in seasonal flower initiation in the adult phase of poplar, citrus, and apple, because they are highly expressed during the seasonal flowering period (Hättasch et al, 2008;Hsu et al, 2006;Kotoda et al, 2010;Nishikawa et al, 2007). Because there is a lack of information on the relationship between AGL6 homologs and seasonal flower initiation, seasonal changes in MdMADS11 gene expression were analyzed in adult apple trees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the present results indicate that the expression patterns of RpFT, RpLFY, RpTFL1, and RpAP3 correspond with morphological changes during floral development of 'Oomurasaki'. Interestingly, with regard to the relationship between floral development and the expression pattern of flowering-related genes, Hättasch et al (2008) reported that if the expression pattern of FT, AFL, and TFL1 homologs in apple shoots was investigated by quantitative transcription analysis, the timing of floral bud formation could be identified. In evergreen azalea 'Oomurasaki', the expression pattern of RpFT, RpLFY, RpTFL1, and RpAP3 was used to determine the period of floral bud formation.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes are involved in the critical phase of flower development and their effect in flower induction is probably influenced by the level of fruit set (Hattasch et al 2008).…”
mentioning
confidence: 99%